Experimental research on production law of multilayer heterogeneous reservoirs - Deng, Xuan; Huang, Xiaoliang; Ye, Qing; Li, Sainan; Yu, Chengchao; Zhang, Xu; Wang, Zuohao (Frontiers in Earth Science, 2022)
In the development of multi-layer co-production heterogeneous reservoirs, problems such as serious inter-layer heterogeneity and interference always exist, resulting in an unclear understanding of inter-layer production. A clear understanding of the interference mechanism and influence of main controlling factors of multi-layer heterogeneous reservoirs on the production of small layers is the key to the effective development of the reservoirs. On the basis of clarifying the main controlling factors affecting the production of multi-layer heterogeneous reservoirs, this paper developed a multi-pipe parallel displacement experiment system to carry out indoor heterogeneous reservoir multi-layer water injection flooding experiments. Combined with dynamic and static parameters, the experiments simulated and evaluated the effects of factors such as permeability ratio, water cut, shutting down high permeability layers, production pressure difference, and change in crude oil viscosity in high permeability layers. The primary objective of this work is to reveal the mechanism of small-layer interference under different conditions, and clarify the influence of main control factors on the production of small-layer. The results show that the smaller the permeability ratio is, the weaker the difference in physical properties among layers along the vertical direction is. The reduction in the difference in seepage resistance decreases the dynamic interference among layers. The reduction in the water ratio among layers and shutting down high permeability layers can reduce the interlayer interference effectively. Increasing production pressure difference effectively improves the oil displacement efficiency of reservoirs with poor physical properties. A lower fluidity in the high permeability layers can effectively improve the oil displacement efficiency of other layers.